Factors influencing India’s fertility patterns and differential of women - Brahma, Jasmine; Basumatary, Konita (Journal of Social Economics Research, 2024)
The study aims to identify the factors influencing fertility patterns and differentials in India while taking into account background characteristics such as place of residence, educational attainment, and religious affiliation. The data used for this study comes from all five rounds of the National Family Health Survey. To calculate the Total Fertility Rate and other factors, including place of residence, educational attainment, and religious affiliation, the background data from the National Family Health Survey was analyzed. Interpolation was used to fill up the gaps left by the missing data. The information from the 25 states was collected. Using the Eviews 12 program, a model based on panel data is performed to pinpoint the factors influencing the patterns and differences in fertility. The place of residence, educational attainment, and religious affiliation, usage of contraception, sequence of births, first marital age, birth period, unmet requirements, and gender attitudes of the couples were all found to have an impact on fertility differences. The results of the panel regression study showed that the interaction of numerous factors caused TFR to differ amongst Indian states. Additionally, it is highly important to look into district-level data.